ANALISIS SUBSEKTOR PERIKANAN DAN FAKTOR-FAKTOR YAN G MEMPENGARUHI PRODUKSI HASIL TANGKAPAN (Studi Kasus di Kabupaten Kepulauan Aru) - , Armand Walay, Artidiatun Adji, M.Ec,. M.A,. Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine and analyze the economic base sectors in enhancing regional economic growth and analyze the factors that influence the production of fish (the catch) fishing in the Regency of Kepulauan Aru. The data used in this research is a primary data with a sample of forty fishing boats and secondary data Gross Domestic Regional Income, Government Original Receipt, exports, employment and data supporting the fisheries subsector over the period 2009-2012. Analysis methods in use LQ analysis, the analysis of MRP, overlay analysis, RPP analysis and multiple regression analysis using the Cobb-Douglas production function with bound varibael that fish production, while the independent variables, namely: the power of engines, fishing gear, crew, and fishing area and dummy IUP. The results showed the proportion of fisheries subsector with an average value of LQ greater than one is 2.72. Overlay analysis explained in 2011 the fisheries subsector activity is dominant both in terms of growth and contribution. The average value of RPP 1.43, the greater the ratio, the more people who work in the fishery subsector. The results of the regression of each independent variable indicates the elasticity of strength machines, fishing gear and the crew have a positive and significant effect on fish production. R-square value of 0.84 indicates the variation of the independent variable in the model is able to explain the effect of 84 percent of the fish production variables and the remaining 16 percent is influenced by variables outside the model in this study.